Model‐informed bridging of rivaroxaban doses for thromboprophylaxis in pediatric patients aged 9 years and older with congenital heart disease - Stefan Willmann; Ibrahim Ince; Maurice Ahsman; Katrin Coboeken; Yang Zhang; Kirstin Thelen; Dagmar Kubitza; Peter Zannikos; Wangda Zhou; Liza Miriam Pina; Teun Post; Jörg Lippert (Wiley, 2022)
Abstract Rivaroxaban is approved in various regions for the treatment of acute venous thromboembolism (VTE) in children aged between 0 and 18 years and was recently investigated for thromboprophylaxis in children aged between 2 and 8 years (with body weights <30 kg) with congenital heart disease who had undergone the Fontan procedure. In the absence of clinical data, rivaroxaban doses for thromboprophylaxis in post‐Fontan children aged 9 years and older or ≥30 kg were derived by a bridging approach that used physiologically‐based pharmacokinetic (PBPK) and population pharmacokinetic (popPK) models based on pharmacokinetic (PK) data from 588 pediatric patients and from adult patients who received 10 mg once daily for thromboprophylaxis after major orthopedic surgeries as a reference. Both models showed a tendency toward underestimating rivaroxaban exposure in post‐Fontan patients aged between 2 and 5 years but accurately described rivaroxaban PK in post‐Fontan patients aged between 5 and 8 years. Under the assumption that hepatic function is not impaired in post‐Fontan patients, PBPK and popPK simulations indicated that half of the rivaroxaban doses for the same body weight given to pediatric patients treated for acute VTE would yield in pediatric post‐Fontan patients exposures similar to the exposure observed in adult patients receiving 10 mg rivaroxaban once daily for thromboprophylaxis. Simulation‐derived doses (7.5 mg rivaroxaban once daily for body weights 30-<50 kg and 10 mg once daily for body weights ≥50 kg) were therefore included in the recent US label of rivaroxaban for thromboprophylaxis in children aged 2 years and older with congenital heart disease who have undergone the Fontan procedure.